Chromium-Salen Catalyzed Cross-Coupling of Phenols: Mechanism and Origin of the Selectivity - Nieves-Quinones, Yexenia (J Am Chem Soc, 2019)
A highly chemoselective phenol cross-coupling reaction catalyzed by a Cr-salen catalyst was developed. Kinetic studies showed that the oxidation of Cr(III) to Cr(V) is the rate-determining step of the reaction. In addition, experimental stoichiometric analysis showed that a high valentCr(V) specie is the active catalyst for this process. The selectivity of the reaction was found to be determined by the cross-coupling carbon-carbon bond forming reaction, rather than any pre-coordination species. It appears that the lowest energy cross-coupling pathway requires a lesser degree of electronic reorganization in its transition state vs the lowest energy homo-coupling pathway. This result was supported by stoichiometric Cr(V) kinetics, (13)C kinetic isotope effects, and DFT calculations. The understanding of the full landscape of this reaction, allowed us to develop a general analysis to predict the regioselectivity of the cross-coupling reaction.